The El Kala wetlands of Algeria and their use by waterfowl - Skinner, J; Smart, M (Wildfowl, 1984)
The El Kala wetland complex in northeast Algeria is of equivalent importance to better-known Mediterranean wetlands such as the Camargue and Coto Doana. Large numbers of waterfowl winter on the varied mosaic of lakes and marshes. During two short visits in December 1981 and December 1983, preliminary enquiries were made into the use made of the area by waterfowl, with special reference to the effects of disturbance by hunters. The situation at El Kala is compared to that at Ichkeul in Tunisia, and movements of birds, notably Greylag Geese Anser anser, between these two major North African wetlands are described. Some suggestions on possible conservation measures and further research are put forward.